2020
DOI: 10.3758/s13415-020-00800-w
|View full text |Cite
|
Sign up to set email alerts
|

The link between resting heart rate variability and affective flexibility

Abstract: The neurovisceral integration model aims to account for the complex interplay between physiological, cognitive, and emotion regulation processes through their support by common cortico-subcortical neural circuits. According to the model, vagally mediated heart rate variability (HRV) serves as a peripheral index of the functioning of these circuits, with higher levels of resting HRV reflecting more optimal functioning, to support goal-directed behaviour and adaptability to environmental demands. Although increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 45 publications
(113 reference statements)
9
47
0
Order By: Relevance
“…Notably, the sensitivity to suffering is an essential attribute of compassion that involves being responsive to one's own suffering or to other people's emotions (rather than activate defense mechanisms and avoidance), and perceiving when they need help (Gilbert, 2019). Consistently, recent findings show that a more efficient shifting of attention from affective to non-affective aspects of negative information was related to lower resting vmHRV (Grol and De Raedt, 2020). In a compassionate approach, this may facilitate emotional pain awareness, and subsequent decisions for helpful actions.…”
Section: Discussionmentioning
confidence: 67%
“…Notably, the sensitivity to suffering is an essential attribute of compassion that involves being responsive to one's own suffering or to other people's emotions (rather than activate defense mechanisms and avoidance), and perceiving when they need help (Gilbert, 2019). Consistently, recent findings show that a more efficient shifting of attention from affective to non-affective aspects of negative information was related to lower resting vmHRV (Grol and De Raedt, 2020). In a compassionate approach, this may facilitate emotional pain awareness, and subsequent decisions for helpful actions.…”
Section: Discussionmentioning
confidence: 67%
“…Theoretical models of neurovisceral integration suggest a link between cardiac bottom-up and cerebral top-down controlled processing ( Park and Thayer, 2014 ; Grol and De Raedt, 2020 ). Viewed from the perspective of the neurovisceral integration model, any intervention that triggers a coupling between heart, brain and mind should lead to neural activity changes in tightly intertwined brain networks thereby facilitating both, cognitively more flexible processing and physically better adaptability to certain tasks and stressors including emotional stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, reduced vagal tone could reflect the activity of OFC and mPFC, which are associated with cognitive control in relation to suicide attempt (33). Prior studies have demonstrated the association between vagally-mediated resting state HRV and cognitive (34) and affective flexibility (35). Cognitive inflexibility can lead to suicidal behavior during a crisis, in which patients consider suicide the only way to escape their current distress (36).…”
Section: Discussionmentioning
confidence: 99%